Improvement of Researcher’s Performance Through Empowerment, Organization Commitment and Innovation in the Ministry of Home Affairs and Regional Government - Narutomo, Teguh; Luddin, Muchlis R.; Suyatno, Thomas (Research and Development Agency Ministry of Home Affairs, 2019)
This study was about the performance of researchers in the Ministry of Home Affairs’ Research and Development Agency (R & D Unit of the MoHA). This research was motivated by the suboptimal performance of researchers in developing policies in the Ministry of Home Affairs. The purpose of this study was to describe the performance of the researchers and their various efforts on research and development in the Ministry of Home Affairs and Regional Government. This study used Structural Equation Modeling (SEM). The results of this study showed that empowerment has a direct effect on innovation and improvement of the researcher’s performance. This means that more empowerment will lead to an increase in the performance of MoHA and Regional Government researchers indicated by the increase in R & D innovations produced by the researchers. The Organization Commitment had a direct effect on innovation and improvement of the researcher’s performance. This means that a high level of commitment in the organization will lead to an increase in the performance of MoHA and the Regional Government researchers, through the increase in innovations. Innovations had a direct effect on the researcher’s performance. This means that a high degree of innovations will lead to an increase in the researchers’ performance. Together, the increased empowerment and organizational commitment directly influence the performance of researchers. This means that increasing empowerment and organizational commitment at the same time will improve the researchers’ performance. The novelty factor from this study was the theoretical implication that this study strengthens the previous studies, that empowerment directly influenced innovation and enhanced the researchers’ performance, the organizational commitment had a direct effect on researcher innovation and improved the researchers’ performance, innovations directly influenced the researchers’ performance, and that empowerment and the organizational commitment together have a direct effect on the performance of researchers.